1986
DOI: 10.1016/s0140-1971(86)80003-3
|View full text |Cite
|
Sign up to set email alerts
|

Precipitating a crisis: family therapy and adolescent school refusers

Abstract: This paper describes the use of family therapy with adolescent school refusers. School refusal is assessed and formulated from a family systems perspective, and therapy proceeds with the crisis precipitated by insisting on the adolescent's early return to school. Some of the common problems encountered in this approach are considered along with its results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…Clearly, involving the family in the intervention, alongside school staff, is likely to be essential in most cases (Doobay, ). While family therapy has long been advocated for the treatment of school refusal (Bryce & Baird, ; Lask, ; Richardson, ), there continues to be insufficient evidence that such an approach, in isolation, is as effective as individually focused therapies for the treatment of school refusal. Instead, family work is now often seen as more appropriately embedded within a CBT programme (e.g.…”
Section: Treatmentmentioning
confidence: 99%
“…Clearly, involving the family in the intervention, alongside school staff, is likely to be essential in most cases (Doobay, ). While family therapy has long been advocated for the treatment of school refusal (Bryce & Baird, ; Lask, ; Richardson, ), there continues to be insufficient evidence that such an approach, in isolation, is as effective as individually focused therapies for the treatment of school refusal. Instead, family work is now often seen as more appropriately embedded within a CBT programme (e.g.…”
Section: Treatmentmentioning
confidence: 99%
“…Although family therapy techniques are widely advocated for the treatment of school refusal (Bryce & Baird, 1986 ;Lask, 1996), it is rare that these, in isolation, are the preferred approach. In a recent survey of U.S. psychologists, Kearney and Beasley (1994) found that work with families tended to focus upon parent training and contingency management ; family therapy did not register as a key treatment.…”
Section: Family Therapymentioning
confidence: 99%
“…It also helps to promote the family's development of a circular (vs. linear) understanding of the problem (Rhodes, ), which sets the scene for the whole family's participation in the process of change. Exploring past attempts at solutions also yields valuable information about family functioning (Bryce & Baird, ).
The ‘nodal point’ for the Black family appeared to be related to a family life cycle transition: Amy completing school and becoming more separate from the family. Jane's school refusal also provided a shared focus for Terry and Ann, without which I suspected the couple's marital tensions threatened to come to the fore.Jane's school refusal caused conflict between Terry and Ann.
…”
Section: A Systemic Formulation Of the Problemmentioning
confidence: 99%
“…I prompt parents to consider what the young person's future might look like if they do not address the issue; how they foresee the young person's development progressing should they continue to refuse to engage in school, and later work; what it might be like for the family to have the young person remain at home for years to come. Often this line of questioning helps the family to grasp the serious implications of continued school refusal, while at the same time highlighting the possibility that the family may be ambivalent about change (Bryce & Baird, ).
Terry and Ann were uncertain how seriously to take the problem because Jane continued to achieve high grades and lead a healthy social life. We talked about the prognosis and risks of untreated school refusal.
…”
Section: Raise Awareness About the Seriousness Of The Problemmentioning
confidence: 99%
See 1 more Smart Citation